Sophora tonkinensis enhances activation of cGAS-STING pathway and restrains HBV replication - Guo, Yuanyuan; Wen, Jincai; Wang, Xueting; Wang, Xianling; Xu, Yingjie; Huang, Siqi; Lu, Zongliang; Chen, Xiaoyan; Huang, Ang; Ma, Zhijie; Cao, Junling; Zhan, Xiaoyan; et al. (Frontiers in Pharmacology, 2025)
BackgroundCyclic GMP–AMP synthase (cGAS)-Stimulator of interferon genes (STING) signaling pathway plays a vital role in innate immune response. Once activated, cGAS-STING pathway mediates the production of type I IFNs and pro-inflammatory cytokines, triggering antiviral response. The Chinese medicine Sophora Tonkinensis Gagnep. is a commonly used traditional Chinese medicine with the effects of clearing away heat and detoxification, subduing swelling and relieving pharynx. Modern studies have shown that it has antiviral activity, however, its mechanism of action is still not clear.MethodsIn this study, we used the botanical drug Sophora tonkinensis Gagnep. (Fabaceae) and investigated the effect of Sophorae tonkinensis extract (STE) on the activation of the cGAS-STING pathway in BMDMs and THP-1 cells, the mechanism by which STE regulates cGAS-STING pathway were studied. We also evaluated the antiviral activity of STE in an HBV mouse model by hydrodynamic injection of pAAV-HBV1.2 plasmid. The content levels of HBsAg and HBeAg in the serum of mice were detected by Elisa, and the level of HBV-DNA was detected by PCR-Fluorescence Probing in One-Tube.ResultsSTE effectively promoted the activation of the cGAS-STING pathway in BMDMs and THP-1, but had no effect on cytoplasmic RNA-induced RIG-I signaling activation. Furthermore, STE can be effective, promoting 2′3′-CGAMP synthesis. Importantly, STE could effectively restrain HBV replication and promote cGAS-STING pathway activation in HBV mouse model.ConclusionSTE could effectively promote the activation of cGAS-STING pathway by facilitating cGAMP synthesis by cGAS, exhibiting obviously inhibitory effect on HBV replication. STE might serve as an effective therapeutic approach against viral infections diseases.